Central Bank Independence and Oil Prices Impact on Macroeconomic Indicators - Mukhamediyev, Bulat; Zhamanbayev, Sayat; Mukhamediyeva, Aliya (International Journal of Energy Economics and Policy, 2024)
The central bank’s independence and oil prices can influence macroeconomic indicators. Many articles are devoted to studying their influence on individual macroeconomic indicators. As it turned out, the study’s results depend on the sample of countries and the interval. They can lead to contradictory conclusions: from a negative or positive effect to its complete absence. However, these issues have not been sufficiently studied for post-Soviet countries with peculiarities in their past development. This study examines the impact of central bank independence (CBI) and oil prices on economic growth, inflation, and income inequality in post-Soviet and developed countries from 2001 to 2020. Based on the analysis of panel data, it was found that strengthening the independence of central banks does not significantly impact economic growth, inflation, and income inequality in developed countries but contributes to their reduction in post-Soviet countries. Higher oil prices reduce economic growth and increase income inequality in developed countries and reduce economic growth, but do not affect income inequality in post-Soviet countries. An increase in oil price increments increases inflation in both samples of countries. The results of this study may be useful for developing macroeconomic policies.